Fixed combination of palmitoylethanolamide and melatonin in preventive therapy of migraine: results from a randomized clinical trial - Piccolo, Vincenzo; Marzocchi, Adua; Maisto, Maria; Summa, Vincenzo; Tenore, Gian Carlo; Amoresano, Angela (Frontiers in Nutrition, 2025)
IntroductionMigraines are neurological disorders which significantly impact quality of life. Current pharmacological treatments often have adverse effects, prompting the search for alternatives with fewer side effects. Several studies have described the antimigraine properties of palmitoylethanolamide (PEA) and melatonin.Materials and methodsOur research assessed the efficacy of the association of hydrodispersible PEA (1,200 mg) and melatonin (0.2 mg) by a randomized, three-month, double-blind, placebo-controlled trial (PEATONIDE®; n = 30 patients; placebo; n = 30 patients). The participants were recruited by “I.N.B.B. Consortium” in Italy. The primary outcome was the reduction of migraine frequency, while secondary outcomes included the reduction of intensity, duration, and grade of disability. The parameters were assessed by a self-reported daily headache diary.ResultsThe formulation displayed a significant reduction in frequency (T3 months: 2.2 ± 0.4 MMDs; T0 baseline: 3.4 ± 0.5 MMDs, ***p < 0.001 vs baseline T0) and duration, intensity, disability, and incidence of associated symptoms of migraine attacks after 3 months of treatment. No adverse effects were observed during the treatment. In addition, a significant mitigation of migraine-related symptomatology was observed.ConclusionThese findings suggest that PEATONIDE® may be a promising adjunctive approach for migraine management. However, given the relatively small sample size, further large-scale and multicenter trials are needed to confirm its clinical applicability in broader migraine population.